Experiencia en Didáctica de la Literatura para el desarrollo de la competencia literaria: un recital de poesía en el grado de Maestro en Primaria - Allué Villanueva, Consuelo (Huarte de San Juan. Filología y Didáctica de la Lengua, 2014)
In this article we want to gather the experience in Teaching of Children’s and Young people Literature by the students of the Master Degree in Primary Education: a poetry reading with the poet Javier Asiáin which took place in the usual classroom College, and reflections and findings which resulted later. We have reviewed the portfolios handed by the students at the end of the course, as part of their work for the course, and culled the comments and reflections related to the poetry reading. Taking into account the careful reading of portfolios and the poetry reading comments, we specify nine objectives in which they agree when they express what has served them Asiáin poetry reading for. We can deduce what use can be achieved in these ways, by using poetry and by using poetry in the classroom.
Keywords: Teaching Literature; poetry reading; portfolios handed; poetry; recite